Characteristic of duplex doppler renal hemodynamics in patients with diabetes mellitus type 1 - Yu. A. Kabirova; A. B. Merinov; T. V. Saprina; I. N. Vorozhtsova; V. D. Zavadovskaya; M. A. Zorkaltsev (Бюллетень сибирской медицины, 2012)
34 patients with diabetes mellitus type 1, who have been diagnosed diabetic nephropathy varying degrees of severity were  examined. Assessment of renal hemodynamics with the help of ultrasound examination of the renal arteries with the use of the Doppler techniques. Revealed violations of the high-speed indicators at the level of interlobar and arc renal arteries, which as the progression of diabetic nephropathy will be revealed in the blood vessels of the kidney over a large caliber (segmental and stem). Significant difference of the resistance index compared with the control group were not found.